The Outcome of Primary Hepatic Carcinoid Tumor: A Retrospective Study Based on Propensity Score Matched Survival Analysis - Jiang, Shaotao; Wu, Huijie; Fu, Rongdang; Mai, Jialuo; Yao, Jiyou; Hua, Xuefeng; Chen, Huan; Liu, Jie; Lu, Minqiang; Li, Ning (Frontiers in Oncology, 2021)
Background Primary hepatic carcinoid tumor (PHCT) is rare and has unclear clinical characteristics and prognosis. Methods A retrospective study using data from the SEER database for patients diagnosed with PHCT used univariate and multivariate Cox models to screen for independent prognostic factors. The outcomes of patients in the surgical and nonsurgical groups were compared, and Propensity Score Matching (PSM) analysis was used to reduce confounder bias. Results A total of 186 PHCT patients were identified and the median survival was 65 (95% CI [43.287, 86.713]) months. Tumor size(HR = 2.493, 95% CI[1.222,5.083], p = 0.012), male(HR = 1.690, 95% CI[1.144,2.497], p = 0.008), age(HR = 2.583, 95% CI[1.697,3.930], p < 0.001), SEER stage(HR = 1.555, 95% CI[1.184,2.044], p = 0.002) and surgery(HR = 0.292, 95% CI[0.135,0.634], p = 0.002) were significantly correlated with patient prognosis. In multivariate analysis, sex(HR = 3.206, 95% CI[1.311,7.834], p = 0.011) and surgery(HR = 0.204, 95% CI[0.043,0.966], p = 0.0045) were independent predictors of patient prognosis. Females are potentially susceptible to PHCT but have a better prognosis. With consistent baseline data, surgical patients have a better prognosis. Conclusions PHCT is uncommon and survival time is longer than that of other primary liver cancers. We found that none-surgery was potentially independent risk factors for poor prognosis.